Investigation of corrosion-resistant properties of aurantium oil in 1 M HCl - Bendaha, H.; Elmsellem, H.; Aouniti, A.; Mimouni, M.; Chetouani, A.; Hammouti, B. (Фізико-хімічна механіка матеріалів, 2016)
The fresh peel essential oils of citrus aurantium from Eastern Morocco (Oujda) have been analyzed by gas chromatography and gas chromatography–mass spectrometry. The analyzed essential oil consist mainly of monoterpene hydrocarbons (54.38%), with limonene (52.67%) being the major constituent. The effect of addition of citrus aurantium essential oil on the corrosion of steel in 1 M HCl acid has been studied by weight loss measurements, potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) measurements. The inhibition efficiency has been found to increase with inhibitor content to attain 95% (at 5 g/l). Data obtained from EIS studies have been analyzed to determinate the model inhibition process through appropriate equivalent circuit models. Inhibition efficiency obtained by the various methods is in good agreement. The adsorption of natural products on the steel surface has been found to obey the Langmuir’s adsorption isotherm.